DEVELOPMENT OF ROLLING STOCK BRAKES (Transport systems and technologies, 2018)
The article deals with the scientific and practical aspects of the formation and development of pneumatic systems of automatic brakes, which were used on the railways of America, Europe and Asia since the 80's of the XIX century. Researches of design features of brake systems of passenger and cargo rolling stock of leading world firms on brake equipment, such as Westinghouse, Kunze-Knorr, as well as less common Gardie, Fif Lille, New York and some others .The further development of braking systems with brake control, depending on the speed of the train, and the presence of anti-fog protection and the use of disc brakes and the use of electrical sensors of anti-earth protection and speed control subsystems are presented. Also in the article the development of brake systems on the railways of Ukraine during the XX century in accordance with the development of the railways of the USSR was considered, and the characteristics of the braking systems were given depending on the propagation speed of the brake wave.
Keywords: brake systems, air distributor, brake cylinder, car, anti-theft protection, speed regulation, disk brake.